Understanding the professionally risky behaviour of young adults in using social media - Carter, Chris James (2016)
Social media play an increasingly important role in people's professional as well as personal lives, providing the means for seeking employment, consolidating social relationships with colleagues, and building professional reputation. However, in doing so, people submit their digital presence to the scrutiny and judgment of both current and prospective employers. This poses risks to professional reputation, and particularly for young adults who have been found to engage in professionally risky behaviour when using social media, despite appearing aware of the potentially damaging reputational consequences. A mixed methods approach was adopted across five empirical studies to examine potential factors influencing this behaviour, and subsequently, how reputational risk may be mitigated in the use of social media amongst young adults. The first two studies, a document analysis of 30 organisational social media policies and a thematic analysis of 14 semi-structured interviews with university employees, emphasised the need for employees to closely self-regulate both the content of their posts and their online of connections with others. Expressions of individuality and personal views on social media were identified as representing both threats and opportunities for professional reputation, emphasising the need for vigilance and careful consideration of professional consequences, even within restricted online spaces. The third study examined whether individual differences in personality traits associated with “professionally appropriate” online behaviour predicted the extent to which 210 Sixth Form College and undergraduate students considered the professional consequences of their social media use. No significant effect of personality was found, although students transitioning into their final year of study reported significantly greater consideration than students at other stages of study. Examining whether increased perceptions of professional audience may have been a factor, the fourth study surveyed 257 final-year undergraduates and found that when employer surveillance on Facebook was judged by young adults to be psychologically closer to immediate experience, perceptions of profession risk in relation to controversial or anti-social content upon the site were greater. In contrast, this was not the case for content depicting poor spelling or grammar, where typically low risk perceptions suggested a potential “blind spot” in risk awareness. The fifth study involved 20 semi-structured interviews with graduate trainees and interns, finding that advice from parents and university careers services was particularly influential in increasing perceptions of professional risk whilst applying for jobs, and connecting with other professionals online became a salient factor following organisational entry. The findings of this thesis demonstrated limited support for either a lack of digital reputation management skill or dispositions towards particular personality traits as factors influencing the professionally risky online behaviour of young adults. In contrast, the findings indicated a role for the psychological distance with which young adults construed professional audience online, and the aforementioned gap in risk awareness. These findings imply that interventions should focus primarily on building awareness of professional risk associated with poor spelling and grammar, whilst focusing more upon ways to induce psychological proximity of professional audience for addressing behaviours where the professional risks are already understood. In doing so, however, it is concluded that the shorter-term benefits of helping young adults to maintain their employability must be balanced against the longer-term consequences of normalising the chronic self-censorship of individuality amongst members of this cohort.